Equine and animal cognition reference database - Krüger, K.
This literature database is maintained by the University of Regensburg - Department of Biology (UREG). You're welcome to send any questions or suggestions to our feedback address. The database is powered by refbase, an open source database front-end for managing scientific literature & citations.